Time, Power, and Religion: Comparing the Disputes over Temple Mount and the Ayodhya Sacred Sites - Cesari, Jocelyne (Journal of law, religion and state, 2021)
Abstract The main argument of this paper is that the sacred time and space of the nation has displaced the meaning of sacredness of the religious sites, and legitimized the national community. By comparing the Temple Mount and Ayodhya disputes, the paper exposes the tensions between two polarities, sacred/profane and religious/political, which helps explain the influence of national identities on the contested sacredness of religious sites. The competition over the Temple Mount is nested within a “thicker” context of conflicting political claims over Jerusalem and national territory between Jewish groups on one hand and between Jews and Muslims on the other. The Ayodhya disagreement is related to the political tensions between the dominant and the minority religions, which have turned the religious dispute over a holy site into a debate on the sacredness of the national community.